2007
DOI: 10.1080/09513590601152177
|View full text |Cite
|
Sign up to set email alerts
|

Effects of postmenopausal hormone replacement therapy on body fat composition

Abstract: The three different types of HRT have comparable effects on central fat tissue in women at increased risk of anthropometry-related CVD. Indeed, the three combinations of HRT reduced fat tissue in the central part of the body. However, the overall effect of HRT was more marked in women with WC > or =88 cm and subcutaneous fat > or =33 cm. Whether HRT increases body weight depends on the body composition indices of individuals before treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…Oral or transdermal hormone therapy use is associated with lower waistcircumference and subcutaneous fat measurements [15,16]. In the present study, visceral adiposity was lower among women who used tibolone; no previous studies have documented this finding.…”
Section: Discussionmentioning
confidence: 67%
“…Oral or transdermal hormone therapy use is associated with lower waistcircumference and subcutaneous fat measurements [15,16]. In the present study, visceral adiposity was lower among women who used tibolone; no previous studies have documented this finding.…”
Section: Discussionmentioning
confidence: 67%
“…23 The effects of CE/BZA on body weight and BMI in the current analyses are also consistent with most previous observations that estrogen plus progestogen therapy prevents postmenopausal weight gain. 7,[9][10][11] One exception is that norethisterone acetate, NETA, one of the more androgenic progestogens 24 in combination with estradiol, has been associated with weight gain in postmenopausal women. One survey of Swedish women taking continuous or sequential oral estradiol (2 mg) with NETA (1 mg) reported that weight gain was the cause of HT discontinuation in 20% to 30% of participants.…”
Section: Black Et Almentioning
confidence: 97%
“…7 However, clinical evidence indicates that women taking menopausal HT do not experience increased weight gain compared with women who are not taking HT, and several studies have shown that HT actually prevents postmenopausal weight gain. [7][8][9][10][11][12][13] A novel, new approach to menopausal therapy is the use of a tissue selective estrogen complex (TSEC), which partners one or more estrogens with a selective estrogen receptor modulator (SERM). 14 One TSEC that specifically pairs conjugated estrogens (CE) with the SERM bazedoxifene (BZA) has been evaluated in a series of phase 3 studies known as the Selective estrogens, Menopause And Response to Therapy (SMART) trials.…”
mentioning
confidence: 99%
“…A number of studies have examined the possible relationship between HRT and adiposity [28][29][30]. Yuksel and colleagues found that three different HRT regimens all decreased the waist circumference and the waist-to-hip ratio [28].…”
Section: Adiposity and Hrtmentioning
confidence: 99%